Fabrication and characterization of composite hollow fibre membrane derived from hydroxyapatite cow bone and kaolin. Issue 1 (April 2021) - Najieha Kamarudin, Suraya; Riduan Jamalludin, Mohd; Nor Suhaida Rasman, Siti; Khadijah Hubadillah, Siti; Arif Budiman Pauzan, Mohd; Hafiz Dzarfan Othman, Mohd
Abstract: Due to its superior behaviour, membrane separation has been applied widely towards water and wastewater treatment. Compare to polymeric counterparts, ceramic membrane has become innovation technology nowadays as it can be used both separation and adsorption application. The conventional ceramic membrane made from alumina, however, in view of its high-cost output. As a result, exploring to a cheap ceramic material derived from clay and waste is gaining attention. In this study, hydroxyapatite derived from cow bone waste and kaolin were used as the main materials for the fabrication of ceramic hollow fibre membrane via phase inversion and sintering technique. The membrane composition was varied through kaolin:hydroxyapatite ration into three composition (40:0, 0:40, 20:20). Result showed the ceramic membrane fabricated from 20 wt% kaolin and 20 wt% hydroxyapatite induces excellent performance at water flux of 10168.5 L/m².h and mechanical strength at 13.33 MPa.